Agricultural value chain development for rural economic growth - Shakila, Carissa Dian (Journal of Entrepreneurial Economics, 2025)
Background: This study examines local economic development (LED) strategies in Muktijaya Village, Setu District, Bekasi Regency, Indonesia, with a focus on leveraging the agricultural potential as a key for community empowerment and sustainable growth. The research is grounded in the transformative legal framework established by Law 6/2014 on Villages, which grants villages greater autonomy and emphasizes community participation in development processes. Methods: Utilizing a descriptive qualitative methodology and case study design, the study analyzes secondary data from documentation studies and literature reviews to explore supporting and inhibiting factors, government efforts, and strategic approaches to LED in Muktijaya Village. Findings: Findings indicate that Muktijaya Village has emerged as a significant galangal production center, with a large cultivation area and relatively high productivity. However, the local economy faces persistent challenges, including reliance on conventional farming techniques, limited post-harvest innovation, and restricted market access, which collectively constrain the added value derived from galangal cultivation. Conclusion: The study identifies key indicators for effective LED, such as employment and entrepreneurship opportunities, income improvement, empowerment of micro and small enterprises, partnerships and networking, human resource development, and technology utilization. Drawing on theoretical frameworks from Blakely & Bradshaw and Saragih, the research underscores the importance of comprehensive strategies that integrate yield improvement, processing innovation, and market expansion. Novelty/Originality of this article: The analysis concludes that a holistic approach—combining community empowerment, institutional strengthening, and technological innovation—is essential for enhancing competitiveness, improving livelihoods, and achieving sustainable economic development in Muktijaya Village. The study’s insights are relevant for similar rural contexts seeking to capitalize on local resources and foster inclusive growth through participatory and innovative development strategies.